Clinical Usefulness of PRECISE-DAPT Score for Predicting Bleeding Events in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention: An Analysis From the SMART-DATE Randomized Trial. (May 2020) - Choi, Ki Hong; Song, Young Bin; Lee, Joo Myung; Park, Taek Kyu; Yang, Jeong Hoon; Choi, Jin-Ho; Choi, Seung-Hyuk; Oh, Ju-Hyeon; Cho, Deok-Kyu; Lee, Jin Bae; Doh, Joon-Hyung; Kim, Sang-Hyun; et al.
Abstract : Background: Although the current guidelines endorse the PRECISE-DAPT score (Predicting Bleeding Complications in Patients Undergoing Stent Implantation and Subsequent Dual Antiplatelet Therapy) to inform clinical decisions regarding duration of DAPT in patients undergoing percutaneous coronary intervention, use of the PRECISE-DAPT score to guide duration of DAPT has not been properly validated by randomized trials focused on the population with acute coronary syndrome. This study aimed to evaluate the usefulness of the PRECISE-DAPT score for predicting future bleeding and ischemic events and to compare clinical outcomes of short-term and long-term DAPT duration according to the PRECISE-DAPT score in patients with acute coronary syndrome. Methods: This was a substudy of the SMART-DATE trial (6- Versus 12-Month or Longer Dual Antiplatelet Therapy After Percutaneous Coronary Intervention in Patients With Acute Coronary Syndrome), in which patients with acute coronary syndrome undergoing percutaneous coronary intervention were randomly assigned to either 6- (n=1357) or 12-month or longer DAPT (n=1355). Major bleeding (Bleeding Academic Research Consortium type 3–5) and ischemic (myocardial infarction, stent thrombosis, or ischemic stroke) events at 18 months after the index procedure were compared between the 6- and 12-month or longer DAPT groups, according to PRECISE-DAPT score. Results: The PRECISE-DAPT score was moderately effective at predicting bleeding events (area under the curve, 0.754 [95% CI, 0.655–0.854]; P <0.001). In patients with nonhigh PRECISE-DAPT score (<25, n=1967 [72.5%]), 6-month DAPT was associated with higher ischemic risk (2.7% versus 1.3%; HR, 2.01 [95% CI, 1.03–3.91]; P =0.040; absolute risk difference, +1.3%; P =0.035) with similar bleeding risk (0.4% versus 0.3%; HR, 2.00 [95% CI, 0.37–10.94]; P =0.422; absolute risk difference, +0.2%; P =0.498), compared with 12-month or longer DAPT. Among patients with high PRECISE-DAPT score (≥25, n=745 [27.5%]), 6-month DAPT presented a similar ischemic risk (4.8% versus 3.4%; HR, 1.43 [95% CI, 0.68–2.98], P =0.348; absolute risk difference, +1.5%; P =0.327) but significantly reduced major bleeding risk (0.6% versus 2.3%; HR, 0.25 [95% CI, 0.05–1.17]; P =0.079; absolute risk difference, −1.7%; P =0.045). Conclusions: Consistent with current guidelines, determination of the duration of DAPT according to PRECISE-DAPT score could improve the clinical outcomes in patients with acute coronary syndrome after percutaneous coronary intervention with current-generation drug-eluting stents. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01701453. Abstract : Supplemental Digital Content is available in the text.